Penerapan Media Papan Flanel untuk Meningkatkan Kemampuan Mengenal Lambang Bilangan 1-10 di RA Madani Alauddin - Pratiwi, Dian; Kusyairy, Umi; Marjani Alwi, Besse; Tayeb, Thamrin; Nurhasanah (KHIDMAH: Jurnal Pengabdian Masyarakat, 2025)
The ability to recognize number symbols is an important aspect of cognitive development in early childhood. However, some children still have difficulty recognizing the symbols for numbers 1–10, so an engaging and age-appropriate learning approach is needed. This community service activity aims to improve children's ability to recognize number symbols through the use of thematically designed and interactive flannel boards. The type of community service conducted is service learning through thematic learning support using educational media. The activity was carried out at TK Madani Alauddin in Makassar City, involving 15 children. The effectiveness of the activity was measured through observations of children's engagement and achievement of cognitive development indicators, particularly the ability to recognize number symbols 1–10. The results showed that most children achieved the “very good development” category, indicating that the flannel board medium was effective in helping children understand number symbols concretely. Therefore, the use of educational media such as flannel boards can be recommended as a fun and meaningful learning strategy for counting in early childhood education.